Metabolic Syndrome Components and the Risk of Colorectal Cancer: A Population-Based Prospective Study in Chinese Men - Li, Xin; Chen, Hongda; Wang, Gang; Feng, Xiaoshuang; Lyu, Zhangyan; Wei, Luopei; Wen, Yan; Chen, Shuohua; Wu, Shouling; Hang, Dong; Dai, Min; Li, Ni; et al. (Frontiers in Oncology, 2019)
Background: To investigate the association between metabolic syndrome (MetS) and the risk of colorectal cancer (CRC) in Chinese men, this study was performed based on data from a large prospective cohort study conducted in China named the Kailuan men cohort study. Methods: A total of 104,333 eligible men who participated in biennial examinations at least once from 2006 to 2015 were recruited. Cox proportional hazards regression models were used to estimate the effects of MetS components on CRC risk. Results: During an 824,211.96 person-years follow-up, 394 CRC cases were verified. Participants with high waist circumference (≥90 cm vs. <90 cm) had a significantly higher risk of developing incident CRC (HR=1.32, 95% CI: 1.07-1.64). Compared with participants with no MetS components, the HRs (95% CI) of developing CRC for men with 1, 2 and ≥3 MetS components were 1.53 (1.01-2.32), 1.42 (0.94-2.14) and 1.70 (1.12-2.56), respectively. In addition, a statistically significant trend (P for trend =0.04) of increased CRC risk with an increasing number of abnormal MetS components was observed. Furthermore, compared with no MetS components, the combination of high waist circumference and elevated fasting blood glucose along with normal levels of the other 3 components, showed 126% increased risk of CRC. Conclusions: Our study suggests that CRC risk is correlated with the number of abnormal MetS components in Chinese men. Men with high waist circumference and elevated fasting blood glucose may have a higher CRC risk even if they do not meet the MetS diagnostic criteria.